Perceived acceptability of a prototype toolkit to support patients and informal caregivers to express their perspectives in palliative care conversations - Annet Olde Wolsink-van Harlingen; Jan Jukema; Kris Vissers; Madeleen Uitdehaag; Jeroen Hasselaar; Leontine Groen-van de Ven (PEC Innovation)
Background: Patients and informal caregivers experience challenges to express their personal perspectives in conversations with healthcare professionals (HCPs). A prototype toolkit, which consists of a hardcopy version and a website, was developed to address their challenges. The aim of this study is to gain insight into the perceived acceptability of this prototype toolkit. Method: Patients and informal caregivers end users and HCPs participated in semi-structured individual or group interviews. This resulted in two databases of qualitative data which were thematically analysed. Results: Twenty-two end users and twelve HCPs participated in this study. There is appreciation for the content and use of the prototype toolkit, with the hardcopy version of the toolkit being valued more than the website. Moreover, the use of the toolkit may strengthen end users' power and control and may support HCPs in tailoring communication and care. End users and HCPs recommendations for implementation are to further develop the prototype toolkit, provide HCPs with information, instruction and support and create facilitating conditions in healthcare. Conclusion: High appreciation of the hardcopy version and the practical value are positive indicators of end users'and HCPS perceived acceptability of the prototype toolkit. However, the content of the toolkit is experienced as being too extensive, with the hardcopy version experienced as being incomplete without the website and the website is experienced as being too complicated to use. Further development and testing of the prototype toolkit is required to increase its acceptability by end users and HCPs. Innovation: In this study a Design Thinking approach was used to test study the acceptability of a prototype toolkit by endusers and HCPs. This approach can contribute to a succesfull implementation of the toolkit and its effectiveness.